Faktor-Faktor Yang Mempengaruhi Pertumbuhan Laba Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi - Yulia Setyarini; Nadia Novitasari Setiono (Bulletin of Management and Business, 2021)
Obtaining profit is one of the parameters or ways to assess the company’s performance. The company’s profit is expected to increase from year to year so that the company can continue to operate and expand. The profit growth is influenced by several factors, both internal and external factors. Therefore, the purpose of this study is to determine the effect of total assets turnover, sales rate, debt to equity ratio, firm size and company age on profit growth in manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The object of this research is a manufacturing company in the consumer goods industry sector for the 2015-2019 period. The total population in this study were 53 companies, with the process of determining the sample using purposive sampling method, the companies that became the samples were 24 companies. The data analysis technique used in this study is panel data analysis with the Eviews 10 program. The results of this study indicate that Total Asset Turnover company size partially have a negative effect on profit growth, the sales level partially has a positive effect on profit growth. Meanwhile, the Debt to equity ratio and company age partially have no effect on profit growth.